2015
DOI: 10.1021/acschembio.5b00893
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Spermidine in Growth of Agrobacterium tumefaciens Is Determined by the 1,3-Diaminopropane Moiety

Abstract: The ubiquitous polyamine spermidine is indispensable for eukaryotic growth and cell proliferation. A conserved vital function of spermidine across eukaryotes is conferred by its aminobutyl group that is transferred to a single lysine in translation factor eIF5A to form the essential hypusine post-translational modification required for cellular translation. In direct contrast, although spermidine is absolutely essential for growth of alpha-proteobacterial plant pathogen Agrobacterium tumefaciens, we have found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…Our recent studies have revealed that the polyamine spermidine is essential for growth in Agrobacterium tumefaciens and that this is due to a requirement for its 1,3-diaminopropane moiety (11). In the current study, we isolated Agrobacterium tumefaciens transposon mutants that led to the elevated production of cellulose and increased biofilm formation and found that they were disrupted for the polyamine biosynthetic pathway.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Our recent studies have revealed that the polyamine spermidine is essential for growth in Agrobacterium tumefaciens and that this is due to a requirement for its 1,3-diaminopropane moiety (11). In the current study, we isolated Agrobacterium tumefaciens transposon mutants that led to the elevated production of cellulose and increased biofilm formation and found that they were disrupted for the polyamine biosynthetic pathway.…”
mentioning
confidence: 80%
“…WT, wild type. and accumulates ornithine (11). The mutant does produce low levels of spermidine (see Fig.…”
Section: An Unbiased Screen For Negative Regulators Of Cellulose Prodmentioning
confidence: 95%
See 1 more Smart Citation
“…The CASDC/CASDH pathway was shown to produce Nspd from Dap and Spd from Put in V. cholerae (64); and Spd from Put, and aminopropylcadaverine and bis(aminopropylcadaverine) from Cad in the ␣-proteobacterium Agrobacterium tumefaciens (75). Triamine Hspd can be produced either by HSS, an enzyme related to CASDH, or from the DHS homologue DHSlike HSS (39).…”
Section: Polyamines In Bacteriamentioning
confidence: 99%
“…No specific bacterial SpmSyn has been identified, and it is likely that in some species the Spd biosynthetic machinery can recognize Spd as a substrate to synthesize Spm (75). It has also been claimed that homologues of the plant A. thaliana acl5-encoded aminopropyltransferase TspmSyn found in bacteria are also specific for Tspm synthesis (77); however, it is more likely that those homologues encode agmatine aminopropyltransferase (70), because there are no reports of Tspm in the bacteria that pos-sess Acl5 homologues.…”
Section: Polyamines In Bacteriamentioning
confidence: 99%